Legal Perspective on Compensation From The Impact of Environmental Pollution Through Industrial Activities - Cholilah Hanum; Rizkan Zulyadi; Wenggedes Frensh (Jurnal Hukum Prasada, 2025)
This study examines the legal mechanism of compensation for environmental pollution caused by industrial activities, focusing on the analysis of the provisions in Law No. 32 of 2009 concerning Environmental Protection and Management. The main issues discussed include: the legal consequences of environmental pollution, the legal accountability process by industry players, and the role of local governments, especially the Mandailing Natal Regency Environmental Office, in prevention efforts. The research method used is normative juridical with a conceptual and legislative approach. The results of the study show that environmental pollution results in legal sanctions in the form of administrative, criminal, and civil sanctions. In addition, the principle of absolute responsibility places industry players as parties who are obliged to compensate for losses caused, both material and immaterial. The study also highlights that the legal remedies available to pollution victims are often limited by limited access to justice, inadequate legal awareness, and bureaucratic inefficiencies. In addition, weak enforcement by environmental authorities often undermines the deterrent effect of existing regulations. Therefore, this study recommends strengthening the monitoring and law enforcement system as a preventive and repressive measure in overcoming environmental pollution. Increasing public participation, improving environmental dispute resolution mechanisms, and increasing the capacity of local government agencies is essential to ensure environmental justice and the realization of compensation rights for affected communities.